Loss assessment of fruit and vegetables in selected public markets in Mindanao, Philippines - Secretaria, L. B.; Pasilan, M.V.O.; Sampiano, K. F. S.; Bayogan, E. V. (International Food Policy Research Institute, 2022)
This assessment produced by FRESH Initiative partner Applied Horticultural Institute, in collaboration with University of the Philippines, Mindanao, provides a multi-method assessment of postharvest losses at a market in urban Mindanao. A structured survey that captured a range of information on the source of the produce, transport methods, vendor preferences, and perceived produce losses was administered to fruit and vegetable vendors. Additionally, a postharvest loss assessment was conducted on randomly selected vendors. The report provides evidence of perceived and actual postharvest losses, and identifies how and when in the value chain for this categorization of vendors that interventions could reduce those losses.